The Existence of POLRI in Handling Minor Crimes of Defamation Through Social Media in the Electronic Information and Transaction Law - Manurung, Andreas; Hakim, Abdul; Jannah, Maya (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The progress of information technology has positive and negative impacts; from a legal perspective, many criminal cases related to the social world in information technology occur in Indonesia. Meanwhile, the application of Law in Indonesia only prioritizes the principle of legal certainty and does not reduce the number of crimes that have happened in the State of Indonesia; until now, it has become a burden for the state when every criminal case ends up in prison. Law enforcers, the Police, the Attorney General's Office, and the Supreme Court created a restorative justice approach in applying criminal cases as a settlement mechanism outside the general court based on the principle of Justice. The application of restorative Justice is not always oriented toward criminal punishment. Still, it is more directed at aligning the interests of recovering victims and the accountability of perpetrators of criminal acts.